2021
DOI: 10.1016/j.molcel.2021.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The CTPase activity of ParB determines the size and dynamics of prokaryotic DNA partition complexes

Abstract: ParB-like CTPases mediate the segregation of bacterial chromosomes and low-copy number plasmids. They act as DNA-sliding clamps that are loaded at parS motifs in the centromere of target DNA molecules and spread laterally to form large nucleoprotein complexes serving as docking points for the DNA segregation machinery. Here, we solve crystal structures of ParB in the pre-and post-hydrolysis state and illuminate the catalytic mechanism of nucleotide hydrolysis. Moreover, we identify conformational changes that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(106 citation statements)
references
References 122 publications
3
72
1
Order By: Relevance
“…In previous structures of apo- or DNA-bound ParB/Noc, the equivalent helix α4 consistently folds back to pack with α5 from the same protein subunit (the folding-back conformation) (Figure 3B and Supplementary Figure 2). The swinging-out conformation of helices α4-5 is often associated with the nucleotide-bound state of ParB/Noc instead (Figure 3B and Supplementary Figure 2) 6,7,11,14 . It has been suggested that CTP-binding most likely facilitates the swinging-out conformation of ParB/Noc since nucleotides have been observed to make numerous contacts to both the equivalent α4 and the α4-α5 connecting loop in various ParB proteins 7,8,11,14 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous structures of apo- or DNA-bound ParB/Noc, the equivalent helix α4 consistently folds back to pack with α5 from the same protein subunit (the folding-back conformation) (Figure 3B and Supplementary Figure 2). The swinging-out conformation of helices α4-5 is often associated with the nucleotide-bound state of ParB/Noc instead (Figure 3B and Supplementary Figure 2) 6,7,11,14 . It has been suggested that CTP-binding most likely facilitates the swinging-out conformation of ParB/Noc since nucleotides have been observed to make numerous contacts to both the equivalent α4 and the α4-α5 connecting loop in various ParB proteins 7,8,11,14 .…”
Section: Resultsmentioning
confidence: 99%
“…The swinging-out conformation of helices α4-5 is often associated with the nucleotide-bound state of ParB/Noc instead (Figure 3B and Supplementary Figure 2) 6,7,11,14 . It has been suggested that CTP-binding most likely facilitates the swinging-out conformation of ParB/Noc since nucleotides have been observed to make numerous contacts to both the equivalent α4 and the α4-α5 connecting loop in various ParB proteins 7,8,11,14 . The observation of a swingingout conformation in DNA-bound Noc is therefore surprising, given that CTP was not included in the crystallization drop and that CTP-binding is incompatible with high-affinity binding at the nucleation site NBS 6 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These inverted repeats are clustered around the oriC region [ 8 ]. ParB dimers close around the DNA in a CTP-dependent fashion and spread from parS sites across the DNA [ 13 , 14 ]. Upon CTP hydrolysis, the ParB proteins are released from the DNA and can be loaded again.…”
Section: Introductionmentioning
confidence: 99%